CMMF and STAM-FNet: Multimodal Fusion Architectures for Complex Scene Understanding in Dynamic Environments (Informatica, 2025)
Multimodal perception has emerged as a vital strategy for understanding complex and dynamic environments, where traditional unimodal approaches fail to handle data heterogeneity and occlusion. This paper proposes two multimodal fusion frameworks—CMMF (Cross-Modal Matching Fusion) and STAM-FNet (Spatio-Temporal Attention Multimodal Fusion Network)—to address structural and temporal challenges in complex scene understanding. The CMMF model adopts a three-stage architecture with cross-modal semantic alignment and dynamic weighting, while STAM-FNet introduces spatio-temporal attention layers and 3D convolutions to enhance feature discrimination in dynamic environments. Experiments are conducted on a dataset of 120000 samples covering three application scenarios: urban monitoring, indoor interaction, and transportation hubs. Evaluation is based on standardized metrics including Top-1 Accuracy, F1-score, AUC, Modal Gain Index, and Inference Delay. Compared to SOTA baselines such as ResNet50, Two-Stream Transformer, and MMBT, STAM-FNet achieves up to 15.8% improvement in accuracy and 20% robustness gain under high-occlusion conditions. CMMF maintains superior performance in static tasks while preserving low parameter count (24.3M). This work demonstrates the effectiveness of adaptive multimodal fusion in improving accuracy, efficiency, and fault tolerance in real-world perception systems.